Correlation Between Hypertension and Oral Health Status: A Systematic Review - Farel Zuvarul Luthfan; Sudiarto (Jurnal Kesehatan Gigi, 2026)
Introduction: Hypertension is a chronic medical condition that has a broad impact on overall health, including oral health. Periodontitis is one condition associated with hypertension. Pharmacological interventions for hypertension also have a significant and often overlooked impact on patient’s oral health, yet no systematic review has presented data on the correlation between oral health status and hypertension. This systematic review aims to identify the correlation between oral health status and hypertension. This systematic review aims to identify the correlation between oral health status and hypertension. Methods: Inclusion criteria comprised English-language research articles published within the last five years reporting on the relationship between oral health status and hypertension, sourced from PubMed, the Cochrane Library, and Scopus in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: A total of 11 research articles were identified involving hypertensive patients aged 20–73 years with oral health issues, consisting of 7 cross-sectional studies, 3 cohort studies, and 1 case-control study. All articles reported a significant correlation between hypertension and oral health conditions. The relationship between oral health and hypertension is a complex, bidirectional systemic pathophysiology involving both systemic inflammatory pathways and the effects of pharmacological interventions. Conclusion: There is a significant association between hypertension and oral health conditions.